A control strategy for optimum efficiency operation of high performance interior permanent magnet motor drives - Ojo, O.; Wu, Zhiqiao; Osaloni, F.; Omoigui, Michael (IEEE, 2020)
38th IAS Annual Meeting on Conference Record of the Industry Applications Conference, vol.1, p.604-610